DAMPAK MEDIA SOSIAL TIK TOK TERHADAP PERILAKU SISWA SEKOLAH MENENGAH PERTAMA NEGERI 06 REJANG LEBONG - Susanti, Eli (Pendidikan Agama Islam (S2), UNSIQ Wonosobo, Jawa Tengah, 2023)
This research is motivated by the development of increasingly modern technology, along with the birth of various new technologies such as smartphones, tablets and various other increasingly sophisticated devices, thereby helping students' futures, especially the increasingly sophisticated social media TikTok. . It is widely sought after and used by students. Apart from being used as a means of entertainment, there are lots of uploads that damage students' morals and behavior. This type of research is qualitative descriptive research to systematically describe the facts found based on observations, interviews and other documents. The objects of this research were teachers and students of SMPN 06 Rejang Lebong, and the data collection procedures used were structured interviews and documentation. Data analysis is carried out by reviewing existing data, then carrying out data reduction, presenting data, drawing conclusions and the final stage of data analysis. Data validity using persistent triangulation observations. From the research carried out, the following results were obtained: The impact of Tik Tok social media on student behavior, more negative impacts were seen, such as students not studying enough, playing with cellphones more than opening books. Students also don't care about the environment, gather to discuss viral things on TikTok social media and make videos together and dance together. Students are still very susceptible to being influenced by the environment, not to mention that students are not yet able to control themselves about what is good and what is bad, whereas the Tik Tok application certainly has positive and negative impacts. Students have been using the Tik Tok application for a long time with the sole aim of filling their free time, even as entertainment for them when they get bored after studying. This is of course a very worrying thing for children's future, apart from being used as a means of entertainment, there are lots of posts that damage children's morals and behavior. Therefore, it is necessary for parents to supervise their children in using social media, so that their children's character is maintained as moral, ethical and noble.